Perencanaan Tenaga Kerja Mikro di Tengah Efisiensi Anggaran: Implikasi Terhadap Perekonomian Indonesia - Nisrina Hanifah Santoso; Sabilal Vitro Juliardan; Melia Khosyi Nareswari; Lutpia Zulfa; Devani Rahma Setyaningayu; Rina Rizkiana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research discusses micro workforce planning in Indonesia in the context of budget efficiency and its impact on the national economy. MSMEs, which have a large role as labor absorbers in Indonesia, have to face budget cuts, as planned by the government in 2025, potentially hampering the process of workforce planning that is adaptive, efficient, and based on local needs. This descriptive qualitative approach based on literature study aims to understand and describe the phenomenon in depth, contextually, and holistically. The results show that budget efficiency in micro workforce planning can be achieved through output to input ratio, budget absorption rate, cost per unit of output, program completion time, and output quality. Effective strategies identified include community-based training, utilization of digital technology, and multi-stakeholder collaboration, especially for resource-constrained areas such as in eastern Indonesia. The findings are expected to provide theoretical and practical contributions to the development of human resource management in the micro sector as well as input for the government in formulating HR development policies and inclusive economic growth.